Buckling of 2d Nano Hetero-Structures with Moire Patterns - Saavedra-Flores, E (Elsevier B.V., 2020)
Moire pattern arises from the lattice mismatch between two different nanosheets. The discovery of the Moire pattern has resulted in breakthrough properties in 2D carbon-based nanostructures such as graphene. Here we investigate the impact of a Moire pattern on mechanical properties of bi-layer 2D nanosheets. In particular, buckling instability of 2D carbon-based nano hetero-structures is investigated using atomistic finite element approaches. Nano hetero-structures considered are graphene-hBN (hexagonal Boron Nitride) and graphene-MoS2 (Molybdenum disulphide). Bilayer graphene has also been considered in the buckling analysis, by orienting the individual sheets at moire angle. Atomistic simulation methodology uses elastic beams to represent intra-sheet atomic bonds and elastic springs to represent inter-sheet atomic interactions. The influence of different boundary conditions and sheet length on the buckling of nano hetero-structures has been investigated. The bridged nano hetero-structures are found be displaying higher buckling strength as compared to cantilever sheets. © 2019 Elsevier B.V.